Visceral Leishmaniasis-HIV Coinfection as a Predictor of Increased Leishmania Transmission at the Village Level in Bihar, India - Cloots, Kristien; Marino, Pia; Burza, Sakib; Gill, Naresh; Boelaert, Marleen; Hasker, Epco (Frontiers in Cellular and Infection Microbiology, 2021)
Background : Visceral leishmaniasis (VL) is on the verge of being eliminated as a public health problem in the Indian subcontinent. Although Post-kala-azar dermal leishmaniasis (PKDL) is recognized as an important reservoir of transmission, we hypothesized that patients with VL co-infected with Human Immunodeficiency Virus (HIV) may also be important reservoirs of sustained leishmania transmission. We therefore investigated to what extent cases of PKDL or VL-HIV are associated with VL incidence at the village level in Bihar, India. Methods : VL, VL-HIV, and PKDL case data from six districts within the highly VL-endemic state of Bihar, India were collected through the Kala-Azar Management Information System for the years 2014 – 2019. Multivariate analysis was done using negative binomial regression controlling for year as a fixed effect and block (subdistrict) as a random effect. Findings : Presence of VL-HIV and PKDL cases were both associated with a more than twofold increase in VL incidence at village level, with Incidence Rate Ratios (IRR) of 2.16 (95% CI 1.81 – 2.58) and 2.37 (95% CI 2.01 – 2.81) for VL-HIV and PKDL cases respectively. A sensitivity analysis showed the strength of the association to be similar in each of the six included subdistricts. Conclusions : These findings indicate the importance of VL-HIV patients as infectious reservoirs, and suggest that they represent a threat equivalent to PKDL patients towards the VL elimination initiative on the Indian subcontinent, therefore warranting a similar focus.